Kenya : Third Review Under the Poverty Reduction and Growth Facility Arrangement and Request for Waivers of Nonobservance of Performance Criteria; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Kenya. (IMF Staff Country Reports; Country Report, 2009)
This paper presents findings of the Third Review under the poverty reduction and growth facility arrangement for Kenya. The sharp spending increase budgeted for 2007/08 could exert pressures on domestic prices and compromise project quality, but the authorities are taking steps to mitigate these risks. Authorities are committed to fully implementing the budget only if nonfood inflation remains low and project quality is maintained. Some aspects of governance have improved, but challenges remain. Structural reforms in public financial management need to be broadened and financial sector reforms accelerated.